Streptococcus mutans serotypes and collagen‐binding proteins Cnm/Cbm in children with caries analysed by PCR. (26th February 2019) - Momeni, Stephanie S.; Ghazal, Tariq; Grenett, Hernan; Whiddon, Jennifer; Moser, Stephen A.; Childers, Noel K.
Abstract : Streptococcus mutans, a primary bacterium associated with dental caries, has four known clinical serotypes ( c, e, f and k ). Certain serotypes, the presence of multiple serotypes and strains with collagen‐binding proteins (CBP, Cnm and Cbm) have been linked with systemic disease. Evaluation of S mutans serotype distribution and caries association is needed in the United States. The purpose of this study was to evaluate the prevalence of S mutans serotypes from two cohorts of African‐American children in rural Alabama using three sample types (saliva, plaque and individual S mutans isolates) by PCR detection for association with caries. Detection of CBP was also performed by PCR. In total, 129 children were evaluated and overall prevalence of serotypes were: serotype c (98%), e (26%), f (7%) and k (52%). Serotype c was statistically associated with higher caries scores in older children ( P  < 0.001) and serotype k was statistically more likely in females ( P  = 0.004). Fourteen per cent of children had CBP. Thirteen S mutans isolates from five children tested positive for both CBP. This study is the first to report on the prevalence of S mutans serotypes in a US population using the PCR‐based approach. The frequency of serotype k in this study is the highest reported in any population, illustrating the need for further study to determine the prevalence of this clinically relevant serotype in the US. This is the first study to report S mutans isolates with both Cnm and Cbm in the same strain, and further analysis is needed to determine the clinical significance of these strains. Abstract : This study is the first to report on the prevalence of S. mutans serotypes in a United States population using the PCR based identification approach with 3 sample types. The prevalence of S. mutans serotype k reported herein is the highest reported to date and strains with both collagen‐binding proteins Cbm and Cnm were observed. This study highlights the need for further study of S. mutans serotype k and collagen‐binding proteins in the overall health of patients in the United States.